Understanding a standard approach to the treatment of interstitial cystitis - Sipahi, Mahammad F. K. G. K.; Desai, Jitesh; Bhatt, Ravi; Patel, Sujan; Agarwal, Chetan (International Surgery Journal, 2023)
Background: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic and painful bladder-related disorder which is characterized by pain and urinary symptoms. It is divided into 2 varieties based on morphological findings i.e. presence of Hunner’s lesion (HL) or no Hunner’s lesion (NHL). It can cause other problems like cognitive, behavioural, emotional and sexual symptoms. Grading is done based on Copenhagen classification and following which a treatment is devised which consists of medical or intravesical or surgical therapy. Methods: A prospective, case-control study was done from the period of January 2019 to July 2022, where the patients were treated by a staged and standard approach, following the treatment protocol strictly. Patients were subjected to a cystoscopy and therapeutic hydro-dissection under spinal anaesthesia and oral therapy. If first line doesn’t work, a cocktail was given via intravesical route following which surgery was done. Later for quality-of-life multiple scales are used on day 0 which is the day patient presented and 90 days after the treatment. Results: Majority in earlier phase of disease required only first line of treatment. While with HL intravesical therapy showed promising results. Only a few required surgical interventions. Conclusions: IC/BPS understanding suggest that multifactorial etiology of this disease require phenotypic classification to differentiate between bladder-centric and/or bladder-beyond patho-physiologies. The future research shall focus on exploring IC/BPS pathophysiology underscoring angiogenic and immunogenic abnormalities and evolution of novel therapeutic regimens for this multi-factorial disease.